Políticas públicas baseadas em evidências na área da saúde mental: uma releitura das capacidades estatais técnicas, burocráticas e políticas, em especial na região do Amazonas - Glaúcia Maria de Araújo Ribeiro (2022)
The main objective of this research was to analyze how mental health care is carried out in the State of Amazonas. The hypothesized guideline, considering the management and care model advocated by the psychiatric reform, sought to provide answers to questions such as: The anti-asylum struggle, based on the harm reduction strategy, has consolidated a public policy in the area of mental health or is still incipient? Has the use of evidence-based public policies advanced significantly in order to influence the quality of care for those suffering from psychiatric disorders, or is it still non-existent? The thesis is linked to the hypotheses described and is structured in three chapters. The first chapter outlines the historical-cultural context of madness, the protest movements and the new institutional model in Brazil, describing the persistence of the phenomenon of social exclusion in the face of a precarious and inefficient bureaucratic apparatus in the area of mental health policy, especially in Amazonas, having as a reference the only psychiatric hospital in the region, the Eduardo Ribeiro Psychiatric Center (CPER). The second chapter traces the generating aspects of public policies, both in the historical field and its relationship with the State, as well as in the definition of the theme, the role of institutions and social actors in their stages of elaboration, implementation, execution and evaluation, the and its impact on analytical models and axes, the timeline with the description of the evolution of legal and administrative frameworks on the construction of public policies in the area of mental health in Brazil. The third chapter establishes the conceptual analysis of evidence-based public policies (PPBEs), the use of scientific and empirical evidence in the formulation of public policies, human knowledge as a dynamic process of adopting evidence to solve problems, epistemology in order to judge the value of evidence in the Brazilian legal field. This normative scope of the use of evidence to create public policies in the health area is supported by art. 198 of CRFB/88, in Ordinance n. 2.690/2009 - National Policy for Health Technology Management (PNGTS), and in Decree n. 9.191/2017. The investigation concludes by indicating that State capacities are not restricted to their technical and bureaucratic aspects, but go further by demanding political capacities for effective, effective and efficient participation and integration of institutions, state agents and the community in general in the production of policies evidence-based public policies in the area of mental health.